If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1x + -20 = 0 Reorder the terms: 7 + -20 + -1x = 0 Combine like terms: 7 + -20 = -13 -13 + -1x = 0 Solving -13 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = 0 + 13 -1x = 0 + 13 Combine like terms: 0 + 13 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| .6x-1=.25x+1.5x-3.3 | | -4/7x-16/7 | | 7-x-5= | | x^2-188x+1092=0 | | -2n+38=8(1-4n) | | 5/6×2/5 | | 8x-8=27 | | 4(3x+10)=16 | | 0.2(x+1)+0.5=0.3(x-4) | | 5n+3+5= | | 8(7x-5)=17x-13 | | 4-3*x+2*x= | | -14=-2d | | 0=(x^2-4) | | 240=2w+2w | | (9+2x)3=(3x)+9 | | w^2+10+21=0 | | y=(x+6i)(x-6i)(x-1)(x-1) | | d^2-19de+48e^2=0 | | 6x-7=9x-19 | | -540+(-13.40x)=1500 | | 3(8+7x)=24-x | | 12a+6b-36= | | 7y-45=95 | | 2x^2+6x+8=224 | | y=3x^2-8x+1 | | C-3=-12 | | 280=(18-x)(x)+(20x) | | 60=3x+9 | | 6x^2-11-60=0 | | -540+13.40x=1500 | | -1.6x^2+3.2x+18=0 |